Innovations in data methodologies and computational algorithms for medical applications - Gangopadhyay, Aryya 1962- (Medical Information Science Reference, 2012)
"This book offers the most cutting edge research in the field of medical applications of technologies, offering insights using case studies and methodologies from around the world" - Provided by publisher
Includes bibliographical references and index
Keywords: Aufsatzsammlung